2007
DOI: 10.1002/elps.200600728
|View full text |Cite
|
Sign up to set email alerts
|

Influence of buffer substances and urea on the β‐cyclodextrin‐mediated chiral separation of dipeptides in CE

Abstract: The influence of buffering substances and urea on the beta-CD-mediated chiral separations of the dipeptides Ala-Phe and Ala-Tyr was studied in the pH range of 2.5-3.8. Only minor effects of the buffer substances on the chiral separation selectivity alpha were observed at a beta-CD concentration of 15 mg/mL. In contrast, the selectivity improved at pH 2.5 but decreased at pH 3.8 upon the addition of 2 M urea. Complexation by beta-CD resulted in a shift of the pK(a) values toward higher values which was more pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
35
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 29 publications
3
35
0
Order By: Relevance
“…Only few reports have been published on the effect of urea on the mobilities of the free analytes and the diastereomeric complexes. Although unchanged mobilities were found in the case of BOC-Phe and b-CD as chiral selector [9] decreased values were reported for the enantioseparation of thioridazine by b-CD [16]. Lower thermodynamic pK a values were reported in the presence of urea compared with pure aqueous solutions for weak acids and bases [17][18][19].…”
Section: Introductionmentioning
confidence: 71%
See 3 more Smart Citations
“…Only few reports have been published on the effect of urea on the mobilities of the free analytes and the diastereomeric complexes. Although unchanged mobilities were found in the case of BOC-Phe and b-CD as chiral selector [9] decreased values were reported for the enantioseparation of thioridazine by b-CD [16]. Lower thermodynamic pK a values were reported in the presence of urea compared with pure aqueous solutions for weak acids and bases [17][18][19].…”
Section: Introductionmentioning
confidence: 71%
“…Furthermore, pH-dependent effects were observed. Although improved b-CD-mediated separations of the enantiomers of the dipeptides Ala-Phe and Ala-Tyr were observed at pH 2.5 in the presence of 2 M urea, addition of the compound resulted in a deterioration of the enantioseparations when the pH was raised to 3.5 [8] or 3.8 [9].…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…It has been shown that urea can be used to improve the separation selectivity in miceller electrokinetic chromatography 10 and electrokinetic chromatography with cyclodextrin. [11][12][13][14][15] Yet, there have been no reports about the use of urea for improving the IA-CE resolution by controlling the ion-association of analytes and the interaction reagent. The fine-tuning of the resolution of IA-CE separation of metal complexes was accomplished as a function of the urea concentration.…”
Section: Introductionmentioning
confidence: 99%